2015
DOI: 10.4049/jimmunol.1500704
|View full text |Cite
|
Sign up to set email alerts
|

CCR5-Dependent Activation of mTORC1 Regulates Translation of Inducible NO Synthase and COX-2 during Encephalomyocarditis Virus Infection

Abstract: Encephalomyocarditis virus (EMCV) infection of macrophages results in the expression of a number of inflammatory and anti-viral genes including inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2. EMCV-induced macrophage activation has been shown to require the presence of CCR5 and the activation of phosphoinositide-3 kinase (PI3K)-dependent signaling cascades. The purpose of this study was to determine the role of PI3K in regulating the macrophage responses to EMCV. We show that PI3K regulates E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…In our study, we found that STAT3KO macrophages display strikingly upregulated levels of phosphorylated Akt and Lyn and increased mRNA levels of iNOS and COX-2 in early time points of LPS stimulation ( Figure 2 ). Relevant role of Akt in regulation of iNOS and COX-2 mRNA in STAT3KO macrophages was also elucidated using pharmacological inhibitors which are known to inhibit Akt activity in macrophages [ 57 , 88 , 89 ]. Treatment with BN82002 [ 57 ] and LY294002 [ 90 ] inhibited the mRNA expression of iNOS and COX-2 in STATKO cells stimulated with LPS for 1 h ( Figure 2 h).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that STAT3KO macrophages display strikingly upregulated levels of phosphorylated Akt and Lyn and increased mRNA levels of iNOS and COX-2 in early time points of LPS stimulation ( Figure 2 ). Relevant role of Akt in regulation of iNOS and COX-2 mRNA in STAT3KO macrophages was also elucidated using pharmacological inhibitors which are known to inhibit Akt activity in macrophages [ 57 , 88 , 89 ]. Treatment with BN82002 [ 57 ] and LY294002 [ 90 ] inhibited the mRNA expression of iNOS and COX-2 in STATKO cells stimulated with LPS for 1 h ( Figure 2 h).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that CCR5 influences different aspects of the pathogenesis of viruses belonging to the Picornaviridae family, including Encephalomyocarditis virus (Christmann et al, 2011;Shaheen et al, 2015), Coxsackievirus B3 (Valaperti et al, 2013), and Rhinovirus (Muehling et al, 2018), once CCR5 participates in the regulation of the host immune response during infection by these viruses. Considering the effects of the genetic variant CCR5Δ32 on CCR5 expression and CCR5-related immune responses, it is possible that CCR5Δ32 also shows some impact on EV-related diseases.…”
Section: Enterovirusmentioning
confidence: 99%
“…From what has been observed for HCV and G. duodenalis, it is possible that this stress response also regulates innate immune cell function. Additionally, mTOR has been shown to increase iNOS translation in RAW264.7, peritoneal macrophages, and GM-DCs [86,87]. Therefore, it is conceivable that mTOR inhibition because of pathogen-driven depletion of L-arginine, leads to a reduced iNOS expression which further limits NO production.…”
Section: L-argininementioning
confidence: 99%